Effect of Yoga on Anxiety of Pregnant Women in Bali - Permatananda, Pande Ayu Naya Kasih; Primatanti, Putu Asih; Satyarini, Puteri Litha (Gaceta Médica de Caracas, 2023)
Objective: Anxiety is an obscure and pervasive concern, related to feelings of uncertainty and helplessness. Anxiety can be caused by certain circumstances. One condition that can cause anxiety is pregnancy. During pregnancy, mothers will experience changes in physical and psychological. Anxiety in pregnancy will have adversely affected the physical and psychological state of the mother and fetus. Yoga is one of the recommended exercises for reducing anxiety during pregnancy. The purpose of this study was to determine the effect of yoga on anxiety levels of third-trimester pregnant women at the Bumi Sehat Foundation Clinic.